2020
DOI: 10.18203/2349-3259.ijct20204482
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of variability of electric pulp response threshold in molars: an in vivo study

Abstract: <p><strong>Background:</strong> Electric pulp testers are widely used diagnostic tools in endodontics. Several factors can affect the result of electric pulp test like thickness of enamel and dentin, concentration of sensory fibres (A delta fibres), direction of dentinal tubules, pulp chamber size, neural elements etc. There are very few studies available in the literature which evaluated the variability of electric pulp response in molar teeth, which are more susceptible to caries. Hence aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(31 reference statements)
0
0
0
Order By: Relevance
“…Conversely, a lack of reaction to the EPT stimulus suggests indirectly that pulp may be necrosed or nonvital. Therefore, the EPT is not the true determinant of pulp vitality, as it only offers information on the innervations of the dental pulp and not from the vascular supply [ 6 ]. Certain studies have found that the EPT has high specificity and varying sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, a lack of reaction to the EPT stimulus suggests indirectly that pulp may be necrosed or nonvital. Therefore, the EPT is not the true determinant of pulp vitality, as it only offers information on the innervations of the dental pulp and not from the vascular supply [ 6 ]. Certain studies have found that the EPT has high specificity and varying sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple variables can influence the outcome of the electric pulp test, such as the thickness of enamel and dentin, the extent of sensory fibers (specifically A delta fibers), the orientation of dentinal tubules while the electrode tip is placed, the size of the pulp chamber, the presence of sclerotic dentin, the decrease in neural elements associated with aging, apprehension regarding electric shock, traumatic injuries, and immature tooth/teeth. Consequently, the presence of healthy pulp tissue may be misinterpreted as aberrant pulp tissue and vice versa [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The EPT threshold value is influenced by various factors, one of which is the thickness of the enamel and dentine [ 12 ]. Numerous studies have been conducted to investigate the optimal locations on teeth that exhibit the lowest threshold of response, yielding diverse findings [ 13 , 14 ]. To the best of our knowledge, there is no information in the literature about the level of pain that the individual experienced at various reference sites.…”
Section: Introductionmentioning
confidence: 99%